Analisis Komponen Rear Back-Up Fitting Terhadap Damage Tolerance dan Durability Pada Vertical Tail Pesawat - Fajar Nugroho; Dwi Hartini; Nurfi Ahmadi; Resa Fadhol Ilahi (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2026)
Aircraft structures are subjected to repetitive cyclic loading that may induce fatigue damage and crack propagation, potentially compromising structural integrity and flight safety. This study examines the damage tolerance and durability of the rear back-up fitting, a critical structural component of the aircraft vertical tail. The analysis combines the Finite Element Method (FEM) to identify stress concentration regions with crack propagation simulations using D-CRACK software under representative operational loading spectra. The results indicate that the most critical locations occur at the fastener holes of PSE V03-A and PSE V03-B. PSE V03-A reaches a critical crack length of 287.646 mm after 328,801 flight cycles, while PSE V03-B reaches a critical crack length of 283.427 mm after 756,190 flight cycles. The longer fatigue life observed in PSE V03-B is primarily attributed to the presence of a stiffener, which effectively reduces stress concentration and slows crack growth rates. In accordance with FAR 25.571, the first inspection is recommended at 12,294 flight cycles for PSE V03-A and 15,000 flight cycles for PSE V03-B, followed by periodic inspections every 2,000 cycles. These results provide a quantitative basis for determining inspection intervals and support the development of a damage-tolerance-based maintenance manual to enhance structural reliability, operational safety, and long-term aircraft durability